UTILIZING DISCORD APPLICATION TO PREVENT BULLYING AT THE SCHOOL - Perangin-angin, Alemina Br.; Sumbayak, Desri Maria; Ayuningtias, Niza (Universitas Negeri Medan, 2024)
Bullying is a serious issue within school environments that affects student well-being and the learning climate. This research aims to explore the effectiveness of implementing the Discord application as a tool to prevent and address bullying cases at T.P Daya Cipta Private Junior High School. The research results indicate an increase in student awareness regarding the importance of respecting differences, as well as a decrease in the number of reported bullying cases during the research period. Additionally, school staff reported an improvement in their ability to respond to and address bullying cases effectively through the Discord application. These findings suggest that the implementation of the Discord application can be an effective strategy for preventing and addressing bullying within school environments. This study provides a significant contribution to our understanding of the role of technology in creating safe and supportive school environments for all students.